Methylation of either cytosine in the recognition sequence CGCG inhibits ThaI cleavage of DNA. - Strobl, J S (1984)
ThaI (CGCG) sites which overlap HhaI (GCGC) sites in phi X174 and pBR322 DNA were methylated in vitro with HhaI methylase and S-adenosylmethionine to yield CGmCG, mCGCG or mCGmCG (5-methylcytosine, mC). Methylation of either cytosine in the ThaI recognition sequence rendered the DNA resistant to ThaI cleavage. Rat pituitary cell genomic DNA was digested with ThaI or 2 other known methylation-sensitive enzymes, AvaI or XhoI. After electrophoresis and ethidium bromide straining of the DNA, all 3 enzymes showed the infrequent DNA cleavage characteristic of methylation-sensitive enzymes. Comparison of pituitary growth hormone (GH) genes bearing strain-specific degrees of methylation showed the less methylated gene to be more frequently cut by either AvaI or ThaI. ThaI resistant sites in GH genes were cleaved by ThaI after exposing cells to 5-azacytidine, an inhibitor of DNA methylation. We conclude that ThaI is a useful restriction enzyme for the analysis of mC at CGCG sequences in eukaryotic DNA.